Cool: a postwar aesthetic and mode of being - Walsh, M (2017)
This thesis examines cool and coolness, both as word and as mode of affective deportment. It treats cool as an historical and literary phenomenon in late twentieth-century Anglo-American culture, during the period between 1945 and the present day. From relatively obscure origins among the subcultures of nineteen-forties African-American inner-city communities, this word, and its cognate forms of disposition towards personal and political agency, diffused through society in the course of these six decades to become, by the turn of the 21st century, near ubiquitous: highly visible, highly recognizable, and closely bound up with certain kinds of social cachet and approval. Through literary-critical analysis I aim to challenge and to deepen the accounts provided by the established literature on the topic, including the work of Lewis MacAdams (2001), Dick Pountain and David Robins (2000), Alan Liu (2004), and Ted Gioia (2009). The narrative emerging from these and other sources offers a unidirectional account of cool's passage through the culture, from fringe to mainstream to wide acceptance – a story that belies the more complex and fractured evolution to which literature can grant us access. An account of cool based in literature and literary analysis reveals how social and political forces, as well as individual authorial interpretations and creative misreadings, established a much more uneven interpretive terrain.